Por que aprender isso, professora? Sentido pessoal e atividade de estudo na psicologia histórico-cultural - Asbahr, Flávia da Silva Ferreira [UNESP]; Souza, Marilene Proença Rebello De (Tikinet Edicao, 2014)
This research investigated the process of personal sense attribution to the study activity of students in Elementary School. The theoretical reference is the Historical-Cultural Psychology. It was conducted with students from 4th grade in a public school. The methodological procedures were: observation the daily life of a classroom; learning oriented situations; focus groups; interviews. As a result, we sought to define the analysis unit: the relation between the study activity motives and the objectives of study actions. It is defended the thesis that for the scholar learning to happen, the study actions of the students must have a personal sense correspondent to the motives and to the social meanings of the study activity, towards the human development promotion.

Se investigó el proceso de asignar un sentido personal a la actividad de estudio de estudiantes de primaria. La referencia teórica es la Psicología Histórico-Cultural. La investigación se desarrollo con estudiantes de cuarto grado en una escuela pública. Los procedimientos metodológicos fueron: observación de la vida cotidiana de una clase; situaciones orientadas de aprendizaje; grupos de discusión; entrevistas. Como resultado, hemos tratado de definir la unidad de análisis: la relación entre los motivos de la actividad de estudio y los fines de las acciones. Para producir el aprendizaje escolar, se defiende la tesis de que las acciones de estudio de los estudiantes deben tener un sentido personal correspondiente a los motivos y los significados sociales de la actividad de estudio, en la dirección de la promoción del desarrollo humano.

Esta pesquisa investigou o processo de atribuição de sentido pessoal à atividade de estudo de estudantes do Ensino Fundamental. A referência teórica é a Psicologia Histórico-Cultural. Foi realizada com estudantes de 4a série de uma escola pública. Os procedimentos metodológicos foram: observação do cotidiano de uma turma; situações orientadas de aprendizagem; grupos focais; entrevistas. Como resultado, buscou-se delimitar a unidade de análise: a relação entre os motivos da atividade de estudo e os fins das ações de estudo. Defende-se a tese de que, para que a aprendizagem escolar ocorra, as ações de estudo dos estudantes devem ter um sentido pessoal correspondente aos motivos e aos significados sociais da atividade de estudo, no sentido da promoção do desenvolvimento humano.
Why do I need lo learn this, teacher? Personal sense and study activity in historic-cultural psychology
¿Por qué aprender esto, maestra? El sentido personal y la actividad de estudio en la psicología histórico-cultural
Keywords: School activity; Historic-cultural psychology; Fundamental education; Actividad escolar; Psicología histórico-cultural; Enseñanza fundamental; Atividade escolar; Psicologia histórico-cultural; Ensino fundamental